2014
DOI: 10.1093/ndt/gfu079
|View full text |Cite
|
Sign up to set email alerts
|

The impact of induction therapy on the homeostasis and function of regulatory T cells in kidney transplant patients

Abstract: In kidney transplant patients, repopulation of Treg after rATG and basiliximab therapy is the result of homeostatic proliferation and not of thymopoiesis. These repopulated Treg were functional after both induction strategies; however only after rATG therapy, were increased proportions of Helios(-) methylated FoxP3 Treg found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…Gurkan et al have described a natural Treg expansion earlier after lymphocyte depletion whereas peripheral Treg expansion occurred six months after transplantation (14). Conversely, Bouvy et al have recently shown that the repopulation of Treg after rATG and basiliximab therapy was the result of homeostatic proliferation and not thymopoiesis (20). This is consistent with our own results: the increase in Treg is rather dependent on ATG-induced peripheral expansion, since CD31…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gurkan et al have described a natural Treg expansion earlier after lymphocyte depletion whereas peripheral Treg expansion occurred six months after transplantation (14). Conversely, Bouvy et al have recently shown that the repopulation of Treg after rATG and basiliximab therapy was the result of homeostatic proliferation and not thymopoiesis (20). This is consistent with our own results: the increase in Treg is rather dependent on ATG-induced peripheral expansion, since CD31…”
Section: Discussionsupporting
confidence: 90%
“…This phenomenon could favor the protective role of ATG against acute rejection, although Treg function after transplantation has not been studied in vivo. Bouvy et al demonstrated an in vitro suppressive function of Treg whatever the induction therapy but no difference in the occurrence of biopsyproven acute rejection between ATG and basiliximab in 33 consecutive transplanted patients (20). This Treg expansion could also be interpreted as a compensatory mechanism against the expansion of late stage differentiated T cells.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, induction therapy with either rabbit antithymocyte globulin or basiliximab (IL-2 receptor antagonist) has shown to favor the repopulation of functional Tregs through homeostatic proliferation and not of thymopoiesis. 69 Campath-1H (an anti-CD52 monoclonal antibody) generates an expansion of Tregs when it is administered with rapamycin in patients with kidney transplantation. 70 This effect could be related with homeostatic proliferation upon lymphopenia, as demonstrated in mice.…”
Section: Modulation Of Regulatory T Cells By Pharmacological Immunosumentioning
confidence: 99%
“…While the mTOR inhibitors sirolimus and everolimus were able to be linked to the development of tolerance, calcineurin inhibitors led to a smaller number of Tregs [80] . In a recent study, Bouvy et al demonstrated the different effect of induction therapy with anti-thymocyte globulin (ATG) and the IL-2 receptor antibody basiliximab on the repopulation of Tregs, which was better under ATG [81] .…”
Section: Biomarkers For the Development Of Tolerancementioning
confidence: 99%